2021
DOI: 10.1186/s12888-021-03595-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in verbal and spatial working memory in patients with bipolar II and unipolar depression: an MSI study

Abstract: Background Depressive symptoms could be similarly expressed in bipolar and unipolar disorder. However, changes in cognition and brain networks might be quite distinct. We aimed to find out the difference in the neural mechanism of impaired working memory in patients with bipolar and unipolar disorder. Method According to diagnostic criteria of bipolar II disorder of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Taking an earlier study conducted with patients with Parkinson disease having mild clinical symptoms as an example, it indicated that their spatial WMC was weaker when compared to verbal and visual WMC [ 23 ]. Also, a very recent study investigated the difference between verbal and visual WMC with depressive individuals and found that only spatial WMC of individuals with unipolar depression and bipolar II depression was impaired [ 24 ]. There are some other researches indicating the difference between verbal and spatial WMC in healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Taking an earlier study conducted with patients with Parkinson disease having mild clinical symptoms as an example, it indicated that their spatial WMC was weaker when compared to verbal and visual WMC [ 23 ]. Also, a very recent study investigated the difference between verbal and visual WMC with depressive individuals and found that only spatial WMC of individuals with unipolar depression and bipolar II depression was impaired [ 24 ]. There are some other researches indicating the difference between verbal and spatial WMC in healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle factors greatly interfere with metabolism, circulating adiponectin levels, cognition, and mood. Imbalance in the input/output energy levels due to excessive energy intake and low physical activity levels can lead to increased adiposity, obesity, and diabetes, all associated with reduced circulating adiponectin levels [70][71][72], cognitive impairments [74][75][76], and reduced structural and functional plasticity [74][75][76]. Likewise, chronic psychological stress, which will be thoroughly discussed next, is linked to reduced adiponectin signaling and impaired peripheral and central metabolism.…”
Section: Adiponectin Deficiency Leads To Impaired Neuronal Metabolism...mentioning
confidence: 99%
“…The results from clinical studies involving patients with psychiatric disorders also contributed to the understanding of emotion–cognition link [ 28 ]. Findings from recent literature showed only spatial working memory was impaired in patients with bipolar II and unipolar depression [ 30 ]. From the previous literature, it can be concluded that researchers have not yet reached a consensus regarding the effect of negative emotion on working memory.…”
Section: Introductionmentioning
confidence: 99%